The prehistory of language - Botha, Rudolf P.; Knight, Chris 1942- (Studies in the evolution of language, 2010)
Prominent linguists, cognitive scientists, archaeologists primatologists, anthropologists, and natural scientists examine issues and advances in understanding language evolution, ranging from the co-evolution of language and music to the evolutionary biology of language.